Critical success factors when exporting "vinho verde" - Mendes, Tiago João Grilo (2019)
The wine industry has played a major role in Portugal’s economy for some time, much of it due to wine exports. These are critical for firms and a path to be pursued in the process of internationalization, as it is proven to bring greater profitability and success, in this highly competitive sector. However, entering foreign markets can bring many challenges to a firm, and those should be evaluated and measured, in order to understand how to overcome them. The solution to these obstacles is the main focus of this research, where the critical success factors for wine exporting are assessed, by understanding what the wine consumers’ preferences are when it comes to the purchase decision-making process. This was done for wine in general, Portuguese wine and Vinho Verde, in order to establish a comparison between them, and to conclude what are the success factors for the export of Vinho Verde. Results show that improving the promotion of the region of Vinho Verde and the overall quality of the wines may be the key to higher export success in the wine industry.